The Role of Female Tutors in the Implementation of Emergency Drills Education for Child Protectionin Nonformal Childhood - Chandra Asri Windarsih; Mustofa Kamil; Elih Sudiapermana; Silvia C. Ambag (Universitas Negeri Semarang, 2025)
Background: Female tutors in non-formal education play an important role in guiding children to deal with emergencies. They are not only educators, but also protectors and agents of change. However, this role has not been fully supported, both in training and resources. Research Urgency: The lack of studies on the strategic role of female tutors in emergency training education shows the need for this research. The results are expected to be the basis for strengthening the capacity and protection of children through the empowerment of female tutors. Research Objectives: This study examines the role of female tutors in implementing emergency training education in non-formal children's institutions and strengthens their role in child protection. Research Method: Using a mixed method sequential exploration design in Cimahi City, data was collected through in-depth interviews, observations, document reviews, and questionnaires. Research Findings: These findings suggest that female tutors play an important role in training children for emergencies, with roles distributed as caregivers (15%), educators (20%), gender norm resistance (15%), leaders (10%), agents of change (10%), internalization (10%), participatory training (13%), and contributors to social context (7%). Efforts to strengthen their role include improving education and health, promoting women's participation in decision-making, raising public awareness, and providing child support and protection. However, challenges remain, such as inadequate training and limited understanding of emergency response procedures. This research highlights the need for ongoing training and adequate resources. Research Conclusion: Female tutors play a vital role in preparing children for emergency situations through various strategic roles. Strengthening these roles requires capacity building, increased participation, and continuous support. However, challenges such as limited training and inadequate understanding of procedures highlight the need for ongoing interventions and sufficient resource allocation. Research Novelty/ Contibution: Her contribution lies in the emphasis on women's role in emergency exercises as the foundation of policy development. The novelty of this study is the integration of the maternal instincts of female tutors with technical emergency training to improve child protection in non-formal settings.